Integrating a Mobile English Learning Application and Reflective Learner Diaries: A Classroom-Based Study of First-Year University Students - Herayana, Desi; Hijriati, Sartika (Universitas Muhammadiyah Mataram, 2026)
This study, based on learning practices in English classes at a university, aims to describe changes in students' English skills and explore the development of their independent learning abilities through digital application-assisted learning and reflective learner diaries. The study was conducted on first-semester Biology students taking an English course at an Indonesian university using a one-group pretest–post-test design for three months. During the intervention, students routinely used an English learning application as a means of independent learning and wrote daily diaries reflecting on the material and their learning experiences. The research data included English proficiency test results before and after the intervention, as well as student learner diaries. The analysis showed a trend toward improving students' English skills, particularly in vocabulary and grammar. Furthermore, the learner diaries indicated a growing awareness of their learning process and the emergence of independent learning behaviours. Although exploratory in nature, this study demonstrates that combining a learning application and written reflections has the potential to support the development of both English skills and students' independent learning abilities in heterogeneous university classes